Silver nanowires in poly(methyl methacrylate) as a conductive nanocomposite for microfabrication - Martinez, E.D. (2016)
Fil: Martinez, E.D. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina